2011
DOI: 10.1021/jf2014638
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunoglobulin E (IgE) Binding to Heated and Glycated Ovalbumin and Ovomucoid before and after in Vitro Digestion

Abstract: This study focuses on the effect of heating and Maillard reaction (MR) on the in vitro digestibility and rabbit IgG- and human IgE-binding properties of ovalbumin (OVA) and ovomucoid (OM) to estimate the impact of processing on their allergenicity. With the human sera studied, heat treatment significantly reduced IgE binding to both OVA and OM, whereas MR reduced the IgE binding to OVA but increased IgE binding to OM. In contrast, heat treatment significantly favored OVA digestibility but glycation impaired it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
102
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(118 citation statements)
references
References 42 publications
12
102
1
1
Order By: Relevance
“…The MR reportedly alters IgE binding and mediator release capacities of some food allergens by glycations (3)(4)(5)(6)(7). Evidence has also accumulated to show that some glycation structures of AGEs could function as immune epitopes for dendritic cells (DCs) (8 -11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The MR reportedly alters IgE binding and mediator release capacities of some food allergens by glycations (3)(4)(5)(6)(7). Evidence has also accumulated to show that some glycation structures of AGEs could function as immune epitopes for dendritic cells (DCs) (8 -11).…”
mentioning
confidence: 99%
“…Importantly, receptors expressed on the cell surface mediate antigen uptake and maturation in DCs. It has been suggested that AGEs influence DC maturation via association with RAGE (3)(4)(5). Moreover, we previously demonstrated that AGEs of ovalbumin (OVA, a major egg allergen) produced by thermal incubation with glucose are taken up by DCs via asso-ciation with SR-A and possess higher CD4 ϩ T-cell immunogenicity than the native form of the allergen (11).…”
mentioning
confidence: 99%
“…Ovalbumin (OVA) and ovomucoid (OM) were identified as egg white allergen epitopes, constituting about 54 and 11% of egg white protein, respectively (8,9). OM is heat resistant and has high allergenicity (10,11). It is a well-known trypsin inhibitor (8).…”
mentioning
confidence: 99%
“…Taken together, these clearly could impact on the allergenic potential of food proteins. The effect of processing on allergenicity of proteins has been assessed in the past by determining IgE-binding capacity using immunoassays/immunoblotting (Blanc et al, 2011;Ehn et al, 2005;Jimenez-Saiz et al, 2011;Sancho et al, 2005). In a study by Vissers et al (2011), a very significant decrease in IgE-binding capacity was noted with heated Ara h 1, but its capacity to elicit mediator release from RBL cells was significantly enhanced.…”
Section: Assessing the Effect Of Processing On Allergenicity Of Food mentioning
confidence: 99%